Pelatihan Internet of Things (IoT) Bagi Siswa Ponpes Imam Ibnu Katsir - Putri Madona; Tianur (LPPM UMRI, 2023)
The rapid development of technology has had a significant impact on various aspects of life and indirectly compelled society to adapt to these changes. The need to enhance efficiency, optimize resources, and improve the quality of life has led to the implementation of the Internet of Things (IoT) in all aspects of life. Islamic boarding schools, as one of the educational institutions, are required to be able to meet the challenges of this digital era by producing graduates who not only understand religion but are also proficient in technology. The existence of IoT training is expected to help expand the knowledge of students at the Imam Ibnu Katsir Islamic boarding school, which can potentially be utilized for personal purposes and make a positive contribution to society.